Development of Educational Games as Learning Media for English Learning for Primary Students (Language Circle: Journal of Language and Literature, 2023)
Industrial era 4.0 brought many changes and innovations in the educational field. Technology is one of the things that is highly developed in the 4.0 era, which has a significant effect on the teaching and learning process. Teachers are required to be able to take advantage of this technological development to be involved in the learning process. As well as in teaching English to the young learner in this 21st century learning, the teacher must be able to create a fun learning environment through the help of learning media, which games. This study aims to develop an educational game as a learning media for English learning for primary students as well as the validity of the product. The Design and Development (DD) and ADDIE model, which consist of five stages, are chosen in this study. The validation from the expert uses three experts, and for the user evaluation, this study uses five students as the respondent. The result showed that in expert judgment validation, the media got 89%, and for the user evaluation, the media got 90%. Based on the result, the educational game for 6th-grade primary school students is feasible to be used in English learning as learning media.